Analysis of the Results of Laparoscopic Cholecystectomy in Patients with Acute Cholecystitis - G.N. Rayimov; A.T. Tillaboldiev; Sh.Sh. Dekhkonov; T.I. Ro’zimatov (Zien Journals, 2022)
The urgency of the problem of surgical treatment of acute cholecystitis is due to the non-decreasing incidence rate and stable mortality rates. Advances in endovideolaparoscopic technologies in the diagnosis and treatment of a number of diseases of the abdominal organs (appendicitis, hernia repair ). perforated gastroduodenal ulcers, peritoneal adhesive disease) are undeniable. However, along with undeniable advantages , laparoscopic cholecystectomy (LC) has also posed a number of complex problems for surgeons, one of which is intraoperative complications. Over the years, their frequency has remained stable, unacceptably high and, according to various authors, is 1.5–16.8%. Despite the successes achieved in laparoscopic surgery, in the treatment of cholelithiasis, the prevention of intraoperative complications remains an urgent and complex problem and is not sufficiently covered in the literature.